Evaluation of lauric acid and L-glutamate individually and in combination as pro-nutrient growth promoters in broiler chickens - G PRABAKAR; S SHANMUGANATHAN; R SURESHKUMAR; M GOPI (Indian Journal of Animal Sciences, 2023)
This experimental study aimed to elucidate the effect of dietary supplementation of lauric acid and L-glutamic acid on the production performance and carcass characteristics of broilers. Day-old broiler chicks (160) were randomly divided into four groups. The chicks were fed with four experimental diets, such as control diet without antibiotics (T1), control + 0.1% lauric acid (T2), control + 0.5% glutamate (T3), and control + 0.1% lauric acid + 0.5% glutamate (T4). The experiment was performed for five weeks using standard management practices. The production performance and carcass characteristics were determined. The body weight, feed intake, and feed conversion efficiency showed significant improvement in the treatment group fed with 0.5% glutamate. The carcass attributes, such as pre-slaughter weight, de-bleeding weight, eviscerated carcass weight, giblet weight, and abdominal fat weight were comparable among the treatments. No significant difference among the groups on serum biochemical parameters was observed. Further, the intestinal length was significantly higher in the T3 group. It was concluded that supplementation of 0.5% glutamate as a pronutrient improved the production performance and increased intestinal length without affecting the other carcass characters in broiler chicken.